2009
DOI: 10.1021/bi901498v
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [4Fe-4S]-Containing and Cluster-Free Forms of Streptomyces WhiD

Abstract: WhiD, a member of the WhiB-like (Wbl) family of iron-sulfur proteins found exclusively within the actinomycetes, is required for the late stages of sporulation in Streptomyces coelicolor. Like all other Wbl proteins, WhiD has not so far been purified in a soluble form that contains a significant amount of cluster and characterization has relied on cluster-reconstituted protein. Thus, a major goal in Wbl research is to obtain and characterize native protein containing iron-sulfur clusters. Here we report the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 75 publications
7
93
0
Order By: Relevance
“…5A). This spectrum was indistinguishable from anaerobically purified WhiD from S. coelicolor, reported to contain a 4Fe-4S cluster (27). It also lacked the characteristic broad shoulders (424, 460, and 560 -580 nm) of aerobically purified WhiB7 from M. tuberculosis and WhiD from S. coelicolor proteins reported to have 2Fe-2S clusters (19,23).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…5A). This spectrum was indistinguishable from anaerobically purified WhiD from S. coelicolor, reported to contain a 4Fe-4S cluster (27). It also lacked the characteristic broad shoulders (424, 460, and 560 -580 nm) of aerobically purified WhiB7 from M. tuberculosis and WhiD from S. coelicolor proteins reported to have 2Fe-2S clusters (19,23).…”
Section: Discussionmentioning
confidence: 76%
“…Over 95% of the purified protein was WhiB7 ST , as determined by SDS-PAGE analysis (data not shown). The UV-visible spectrum of anaerobically purified WhiB7 ST was similar to anaerobically purified WhiD (27) and reconstituted WhiB proteins containing 4Fe-4S clusters (23). Removal of the N-terminal His tag by enterokinase did not alter the absorbance spectra (data not shown).…”
Section: Conserved Sequence Motifs Are Required For Whib7mentioning
confidence: 82%
See 1 more Smart Citation
“…Subsequent reduction of the disulfide bond (through a yet unknown mechanism) stimulates disulfide reductase activity. This debate was fueled further when independent groups were unable to detect such activity with WhiB1 or the S. coelicolor orthologue of WhiB3 (13,42), and also when it was reported that Mtb WhiB1 interacts with GlgB (an a-1,4-glucan branching enzyme) to reduce the intramolecular GlgB disulfide bond (20). Although these enzymatic studies are in contrast with increasing evidence suggesting that the Wbl proteins are regulatory DNA-binding proteins (37,40,42), or transcription factors as was recently demonstrated for Mtb WhiB1 (42), it cannot be discounted that WhiB1 may function as a highly selective reductase.…”
Section: Protein Network and Wbl Functionmentioning
confidence: 99%
“…In addition, NO can react with the Fe-S clusters of TCA cycle enzymes, leading to the formation of a protein-bound dinitrosyl-iron complex (DNIC), which can alter enzymatic activity (17). Also, in elegant biochemical studies on Streptomyces WhiD (the homologue of Mtb WhiB3) and Mtb WhiB1, protein stability in the presence of H 2 O 2 and O 2 C- (13) and NO (14) What protects the WhiB3 Fe-S cluster against oxidation and eventually complete loss of the cluster during aerobic growth? One possibility is that a mycobacterial redox buffer in the cytoplasm protects cellular Fe-S clusters.…”
Section: Fig 4 Relative Transcription Profiles Of Mtb Wbl Genesmentioning
confidence: 99%